Psychology in Latin America Current Status, Challenges and Perspectives (Springer International Publishing, 2018)
This contributed volume is a real "who is who" in Latin American psychology. Edited by the most prominent psychology researcher alive in the region, the book presents a comprehensive panorama of psychology in Latin America as a science, as a profession and as a way of improving the quality of life of individuals and communities. Despite its achievements, Latin American psychology is little known by the international psychological community. In order to fill this gap, Dr. Rubén Ardila has invited the most important researchers and practitioners in the region to present an overview of psychology as both a profession and a research field in Latin America in the following areas: · Scientific research · Professional issues · Clinical and health psychology · Developmental psychology · Educational and school psychology · Organizational and work psychology · Social psychology · Community psychology · Legal and forensic psychology Psychology in Latin America - Current Status, Challenges and Perspectives seeks to place Latin American psychology on the map of international psychology, and by doing so it aims to foster cooperation between researchers, practitioners and students from the region with its peers from all over the world. .